2017
DOI: 10.4178/epih.e2017024
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and atrial fibrillation applying the Heaviside function in survival analysis: the Multi-Ethnic Study of Atherosclerosis

Abstract: OBJECTIVESAlthough the effect of physical activity (PA) on the incidence of atrial fibrillation (AF) has been studied, contradictory results have been reported. Such discrepancies may reflect the different effects of various types of PA upon AF, as well as gender interactions. Therefore, we aimed to evaluate the associations of PA types (total, moderate/vigorous, and intentional), as well as walking pace, with AF risk in men and women.METHODSUsing the Multi-Ethnic Study of Atherosclerosis Typical Week Physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…We excluded 24 studies because they (1) assessed the association of PA with AF in competitive athletes (long-term endurance exercise); (2) were designed as retrospective cohorts or case-control studies; (3) were conference abstracts, reviews, or case reports; or (4) focused on duplicate populations. Finally, we included a total of 16 prospective studies [1 post-hoc analysis of RCTs (20) and 15 prospective cohorts (5)(6)(7)(8)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)] representing a total sample size of 1,449,017 individuals and 39,884 AF cases.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 24 studies because they (1) assessed the association of PA with AF in competitive athletes (long-term endurance exercise); (2) were designed as retrospective cohorts or case-control studies; (3) were conference abstracts, reviews, or case reports; or (4) focused on duplicate populations. Finally, we included a total of 16 prospective studies [1 post-hoc analysis of RCTs (20) and 15 prospective cohorts (5)(6)(7)(8)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)] representing a total sample size of 1,449,017 individuals and 39,884 AF cases.…”
Section: Study Selectionmentioning
confidence: 99%
“…The duration of follow-up ranged from 3.7 to 22 years. Nine studies (5,7,8,22,25,26,(29)(30)(31) and 11 studies (5,7,8,20,21,23,25,26,(29)(30)(31) reported the association between PA and AF in males and females, respectively. Apart from the study by O'Neal et al (8), the studies relied on self-reported PA collected by questionnaire or interview.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four studies were prospective (Bapat et al, 6 Grundvold et al, 7 Mokhayeri et al, 8 Morseth et al, 9 and Mozaffarian et al, 10 ) with mean follow-up periods of 7.7, 35, 11, 20 and 12 years, respectively; a cohort study (Williams et al, 14 ) with mean follow-up period of 6.2 years; a Post-Hoc analysis of a prospective study (Everett et al, 13 ), a crosssectional study (Myrstad et al, 11 ) and an observational study (Qureshi et al, 12 ). In addition to these, one was a Post-Hoc analysis of a Randomized Clinical Trial (Aizer et al, 4 ) with follow-up period of 12 years, and a prospective observational study (Azarbal et al, 5 ) with follow-up period of 11.5 years.…”
Section: Study and Characteristics Of Patientsmentioning
confidence: 99%
“…3 Original Article studies report a J or U curve between the correlation of intensity of physical activity and AF. [4][5][6][7][8][9][10] On the other hand, some studies show a linear correlation between the amount of physical activity and the development of AF. [11][12][13][14] Considering the regular practice of physical activity as a cardiovascular benefit and literature inconsistency about its potential arrhythmogenic effect, the objective of this study was to analyze the effects of physical activity on the incidence of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Az aerob testedzés során a paraszimpatikus tónus, a baroreceptorok érzékenysége, valamint a szívizomros-tok kolinerg érzékenysége fokozódik, ami együttesen a pitvari refrakteritás csökkenését előidézve PF-t indukál-hat. Újabban az epidemiológiai adatokon kívül [38] humán biokémiai és MRI-vizsgálatokkal is igazolták [39,40], hogy az elhúzódó bal és jobb pitvari fizikai terhelés és a következményes emelkedett pulmonalis nyomás él-sportolókban fokozott pitvari fibrosist is okoz, amely a PF kiváltásában is szerepet játszik. A nem extrém sportterhelés (testedzés) során megnyilvánuló paraszimpatikus tónusfokozódás ugyanakkor a PF szempontjából protektív hatással is bírhat [5,34].…”
Section: Társbetegségek éS éLetmódbeli Tényezők Szerepe Az Autonóm Idunclassified